Analisis Kualitatif Rhodamin B Pada Selai Strawberry Curah Di Pasar Induk Kajen Dengan Metode Benang Wol Dan Kromatografi Lapis Tipis - Ardiani Rizkiana Wijayaning Tias; Siska Rusmalina (Pena Medika Jurnal Kesehatan, 2023)
Rhodamine B is one of the synthetic dyes that is prohibited in food. However, this substance is still often added to processed food by some persons. The purpose of adding these dyes is to make processed food more attractive, attractive to consumers, and reduce production costs. Rhodamine B that enters the body can cause irritation of the digestive tract, poisoning, impaired liver function, impaired kidney function, and can cause cancer and death. The Kajen Main Market is a meeting place for sellers and buyers to carry out buying and selling transactions. Bulk strawberry jam can be found or purchased at the Main Kajen market. To protect consumers around the Kajen Main Market, it is necessary to research the Rhodamine B content in the jam sold at that market. This research is included in the descriptive observational with a sample of bulk strawberry jam sold at the Kajen Main Market, Pekalongan Regency. Rhodamine B in the sample can be determined using the Thin Layer Chromatography (TLC) method, and wool yarn. Data analysis for the determination of Rhodamine B content using the TLC method was carried out by comparing the Rf value and the appearance of the color of the spots between the samples and the reference standard. A positive result if the Rf value and spot color of the sample and standard have the same result. The wool thread method is based on the bonding of the Rhodamin B color to the fat-free wool thread which is not washed off by water. In this study, from a total of 6 bulk strawberry jam samples, it was concluded that the results of the negative analysis contained the substance Rhodamine B. It can be concluded that it was negative because even thoughthe Rf results of the samples and standard standards were the same, the samples did notshow clear and bright colored spots on the silica plate when viewed through visible light and UV light, the Rf results show the same number, it is assumed that there are other additives that affect these results. In addition, the negative results were also confirmed by the wool yarn test, which also showed a negative result because the sample dyes absorbed into the wool fiber fibers could be washed off by water, unlike the reference standard which still left color on the wool fiber fibers and was not washed off by water. It is recommended to carry out further research in order to know the content of preservatives and saccharin in bulk strawberry jam